Long term outcome after coronary stent implantation: a 10 year single centre experience of 1000 patients. (1st October 1999) - van Domburg, R T; Foley, D P; de Jaegere, P P T; de Feyter, P; van den Brand, M; van der Giessen, W; Hamburger, J; Serruys, P W
Abstract : OBJECTIVE: To describe the long term clinical outcome (up to 11 years) after coronary stenting. DESIGN: A single centre observational study encompassing 1000 consecutive patients with a first stent implantation (1560 stents) between 1986 and 1996, who were followed for at least one year with a median follow up of 29 months (range 12–132 months). RESULTS: Up to July 1997 the cumulative incidence of the major adverse cardiac events (MACE) of death, non-fatal acute myocardial infarction, coronary artery bypass grafting, and repeat percutaneous transluminal coronary angioplasty was 8.2%, 12.8%, 13.1%, and 22.4%, respectively. Survival at one, three, and five years was 95%, 91%, and 86%, respectively. Comparison of MACE incidence during the "anticoagulant era" and the "ticlopidine era" revealed significantly improved event free survival with ticlopidine (27% v 13%; p < 0.005). Multivariable analyses showed that ejection fraction < 50% (relative risk (RR) 4.1), multivessel disease (RR 3.0), diabetes (RR 2.9), implantation in saphenous vein graft (RR 2.1), indication for unstable angina (RR 1.9), and female sex (RR 1.7) were independent predictors of increased mortality after stenting. Independent predictors of any MACE were multivessel stenting (RR 2.0), implantation in saphenous bypass graft (RR 1.6), diabetes (RR 1.5), anticoagulant treatment (versus ticlopidine and aspirin) (RR 1.5), bailout stenting (RR 1.5), multivessel disease (RR 1.4), and multiple stent implantation (RR 1.5). CONCLUSIONS: Long term survival and infarct free survival was good, particularly in non-diabetic men with single vessel disease and good ventricular function, who had a single stent implanted in a native coronary artery. A dramatic improvement was observed in event free survival, both early and late, with the replacement of anticoagulation by ticlopidine. This, of course, cannot be separated from improved stent implantation techniques between 1986 and 1995. Ultimately, almost 40% of the patients experienced an adverse cardiac event (mainly repeat intervention) in the long term. New advances in restenosis treatments and in secondary prevention must be directed at this aspect of patient management after stenting.